INFORMATION SOCIETY BETWEEN THE INTELLECTUAL PROPERTY LAW AND THE PUBLIC DOMAIN - Marković, Slobodan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Аbstract: The information society is ambivalent about intellectual property law. On the one hand, it is the result of technological and economic progress that is (to a certan extent) the result of the operation of intellectual property rights. On the other hand, intellectual property in some aspects begins to limit the usefulness of the available technological capabilities of the information society. Pointing to the sensitivity of the boundary between freedom of competition and exclusive intellectual property rights, that is, public and private domain, the author emphasizes the public domain as a cultural and economic resource that is gaining new meaning in modern technological and economic conditions. Contrary to the legislator’s relative passivity to adjust intellectual property law to the new conditions, there is a process of private reconfiguration of relationships in the information market, which extends the public domain by the abstention of the holders of exclusive IP rights to exercise.